Simulation of lubrication for eccentric-roller of fixed vane rotary compressor - Goh, Aik Ling. (2012)
A new variant of the Rolling Piston Rotary Compressor, also known as the Fixed Vane Rotary Compressor, is presented in this report. The latter is developed to increase energy efficiency by reducing frictional losses during operation. However, its working principle also introduces a significant frictional loss at the rubbing surfaces between the eccentric and roller. Therefore, a detailed hydrodynamic lubrication analysis of the eccentric-roller of the Fixed Vane Rotary Compressor is carried out, using both mathematical and computational models, to solve Reynolds’ Lubrication Equation and optimize the design of the compressor.